An introduction to flapping wing aerodynamics - Shyy, W.; Aono, Hikaru, 1981-; Kang, Chang-kwon, 1978-; Liu, Hao, Ph.D (Cambridge University Press, 2013)
This is an ideal book for graduate students and researchers interested in the aerodynamics, structural dynamics and flight dynamics of small birds, bats and insects, as well as of micro air vehicles (MAVs), which present some of the richest problems intersecting science and engineering. The agility and spectacular flight performance of natural flyers, thanks to their flexible, deformable wing structures, as well as to outstanding wing, tail and body coordination, is particularly significant. To design and build MAVs with performance comparable to natural flyers, it is essential that natural flyers' combined flexible structural dynamics and aerodynamics are adequately understood. The primary focus of this book is to address the recent developments in flapping wing aerodynamics. This book extends the work presented in Aerodynamics of Low Reynolds Number Flyers (Shyy et al. 2008). -- Provided by publisher
Keywords: Aerodynamics.; Airplanes -- Wings.; Micro air vehicles.; Wings (Anatomy); Animal flight.; elektronické knihy; electronic books